Improving the contestability of e-commerce in two jurisdictions: The Amazon case - Fiona Scott Morton (Bruegel, 2023)
Antitrust cases against Amazon in the United States reveal that the e-commerce giant has developed algorithms that mimic price protection contracts called MFNs (from mostfavoured nations, a term borrowed from international trade), despite the company saying publicly that it ended the contracts themselves some years ago. MFNs are well known in antitrust enforcement for their anticompetitive effects: higher prices and less entry. The complaints describe how Amazon demotes merchants from its coveted Buy Box if Amazon finds a lower price on a rival e-commerce site, creating an incentive for merchants to set higher prices on rival sites. the European Union, the Digital Markets Act bans such contracts. This would be a good remedy for the US as well as it would restore competition with minimal harmful side effects. The US complaints describe a different scheme that penalises brands if Amazon must reduce its retail prices to match a rival retailer. The EU may have to pursue this conduct under Article 102 of the Treaty on the Functioning of the European Union that prohibits abuse of dominance. Both the US Federal Trade Commission (FTC) and the European Commission have found that Amazon's policy of tying its own logistics service to Amazon Prime status raises entry barriers to rivals. The European Union remedy redesigns the Buy Box and allows rival logistics services access to consumers. This remedy provides a useful benchmark to consider in designing remedies for the FTC and for California, which is also pursuing an antitrust case against Amazon. In general, both the US and the EU gain from the enforcement actions of the other.
Keywords: 330